Pattern of Communication and Constraints in Disseminating Modern Agricultural Technologies in Arid Villages - Saha, D K; Malhotra, S P; Mathur, Y N; Singh, Ugam (Annals of Arid Zone, 2016)
A study was conducted in two arid villages of Jodhpur district in western Rajasthan to investigate the communication pattern, constraints in communication and credibility of various information sources. However, no major difference was observed between and within the villages with respect to utilization bf various media. Situational and input constraints were predominantly higher in village Doli than socio-psychological and communication constraints. The literate farmers reponed more communication constraints than illiterate farmers. Technical ,persons (e, g. Agricultural scientists in village Doli and village level worker in village Ransigaon) had highest relative credibility.